Top Policy Lessons from Africa Gender Innovation Lab Research - World Bank (Washington, DC, 2017)
The study in Togo reveals that psychology-based entrepreneur training (personal initiative training) increases firm profits by 30 percent, compared to a statistically insignificant increase for traditional business training. Personal initiative training was particularly effective for female-owned businesses, who saw their profits increase by 40 percent, compared to no impact from traditional business training. Getting more women into traditionally male-dominated sectors of the economy could boost the incomes of women entrepreneurs and their households. Our study in Ethiopia revealed that firms owned by women who cross over into male-dominated sectors are two times more profitable than firms owned by women who remain in traditionally female sectors, and they are just as profitable as businesses owned by men. Women are more likely to cross-over when parents and husbands support them and when they have access to information on the higher earnings potential in male-dominated sectors.